2021
DOI: 10.1021/acs.jmedchem.0c01912
|View full text |Cite
|
Sign up to set email alerts
|

Ifenprodil Stereoisomers: Synthesis, Absolute Configuration, and Correlation with Biological Activity

Abstract: Ifenprodil (1) is a potent GluN2B-selective N-methyl-D-aspartate (NMDA) receptor antagonist that is used as a cerebral vasodilator and has been examined in clinical trials for the treatment of drug addiction, idiopathic pulmonary fibrosis, and COVID-19. To correlate biological data with configuration, all four ifenprodil stereoisomers were prepared by diastereoselective reduction and subsequent separation of enantiomers by chiral HPLC. The absolute configuration of ifenprodil stereoisomers was determined by X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Addition of 10 µM glycine and 10 µM ( S )‐glutamate induced a characteristic NMDA‐specific ion current that was inhibited by the application of 10 µM of 21q , 22d , and 22m . [ 31,46 ] To evaluate the activity of the test compounds, the inhibitory activity of ifenprodil ( 1 ) was also recorded at concentrations of 1 and 10 µM. Compounds achieving more than 80% inhibitory activity at 10 µM were tested at a concentration of 1 µM as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of 10 µM glycine and 10 µM ( S )‐glutamate induced a characteristic NMDA‐specific ion current that was inhibited by the application of 10 µM of 21q , 22d , and 22m . [ 31,46 ] To evaluate the activity of the test compounds, the inhibitory activity of ifenprodil ( 1 ) was also recorded at concentrations of 1 and 10 µM. Compounds achieving more than 80% inhibitory activity at 10 µM were tested at a concentration of 1 µM as well.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it was shown that ligands with (R)-configuration at the benzylic position represent the eutomers. [36,46] Therefore, (1R,2R)-Ifenprodil [31] 5.8 ± 1.3 Nd 125 ± 24 98 ± 34…”
Section: Interactions With the Ifenprodil Binding Sitementioning
confidence: 95%
See 1 more Smart Citation
“…As a derivative of phenylalanine, PF74 is prepared from enantioenriched material from natural sources. Although there is a vast body of literature on strategies to avoid epimerisation during peptide coupling [ 15 ], the inherent asymmetry of biological systems necessitates that control of absolute stereochemical configuration of small molecule inhibitors remains integral to their activity [ 14 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] It was shown that the selectivity of ifenprodil depends considerably on the configuration of the two centers of chirality. [29] Moreover, the bioavailability of ifenprodil is rather low due to fast biotransformation, in particular rapid glucuronidation of the phenol. [30] To improve selectivity and bioavailability, the 2-amino-1phenylpropanol substructure of ifenprodil (1) and traxoprodil (2) was rearranged in the class of 3-benzazepines 3 (Figure 1).…”
mentioning
confidence: 99%